2007
DOI: 10.1124/jpet.107.126250
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drug-Induced Neuronal Cell Death in the Immature Brain: Effects of Carbamazepine, Topiramate, and Levetiracetam as Monotherapy versus Polytherapy

Abstract: The aim of this study was to test the potential neurotoxicity of three antiepileptic drugs (AEDs), carbamazepine (5H-dibenzepine-5-carboxamide), topiramate [2,3:4,5-bis-O-(1-methylethylidene)-␤-D-fructopyranose sulfamate], and levetiracetam [2-(2-oxopyrrolidin-1-yl)butanamide], in the developing rat brain, when given alone or in combinations. The extent of cell death induced by AEDs was measured in several brain regions of rat pups (postnatal day 8) by terminal deoxynucleotidyl transferase dUTP nick-end labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
126
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 36 publications
7
126
0
5
Order By: Relevance
“…In this frame, it has been indicated that the therapeutic index of levetiracetam is higher than 5 times and possibly about 10 times higher (20). It has also been indicated in study of Manthey et al that levetiracetam does…”
Section: Resultsmentioning
confidence: 85%
“…In this frame, it has been indicated that the therapeutic index of levetiracetam is higher than 5 times and possibly about 10 times higher (20). It has also been indicated in study of Manthey et al that levetiracetam does…”
Section: Resultsmentioning
confidence: 85%
“…J. S. Kim et al (2007) изучали проапоптозное дейст-вие АЭП (фенитоин, вальпроат и фенобарбитал) в не-зрелом мозге животных, а также эффекты индуциро-ванных (электрошоком) судорожных приступов. Каждый из этих препаратов вызывал выраженную клеточную гибель нейронов в специфических регио-нах мозга, в то время как леветирацетам даже в высо-ких дозах (до 1500 мг / кг) не оказывал подобного действия.…”
Section: безопасность леветирацетама во время беременностиunclassified
“…Ис-следование показало, что некоторые АЭП смещают программируемую клеточную гибель к противополож-ному концу спектра и провоцируют избыточную ги-бель нейронов. Авторы идентифицировали по край-ней мере один АЭП (леветирацетам), который был лишен проапоптозного эффекта в головном мозге младенцев даже в высоких дозах [56].…”
Section: безопасность леветирацетама во время беременностиunclassified
See 2 more Smart Citations